Redox Imbalance and Reproductive Side Effects of Long and Short Term Nitroglycerin Treatment in Rat Uterus - Mostafavi-Pour, Zohreh; Rajabi, Sadegh; Zal, Fatemeh; Zare, Razieh; Akmali, Masoumeh (Novelty in Biomedicine, 2019)
Background: Bioactivation of nitroglycerin (NTG) leads to the production of reactive oxygen species and reactive nitrogen species. The aim of this study was to investigate the effects of NTG treatment on the redox homeostasis in rat uterus around the time of implantation and the number of pups. Materials and Methods: The rats in long-term test groups were treated subcutaneously with NTG (15mg/kg BW) and normal saline (1ml/kg B) in control groups for 4 weeks. Afterwards, they were mated and divided into four groups. Two groups were treated until 5 days after mating. Thereafter, they were sacrificed and the activities of glutathione peroxidase (GPx), catalase (CAT), and glutathione reductase as well as the levels of reduced glutathione (GSH) and malondialdehyde (MDA) in the uterus homogenates were measured. In other two groups, treatments were continued until their pups were counted. In the short-term groups, treatments were started after mating, and all above parameters were measured as similar as long-term groups. Results: Long-term NTG treatment significantly increased MDA level and decreased the GPx activity and the pups number compared to the controls (p<0.05), whereas no marked alteration in the activities of GR and CAT and the levels GSH were observed. However, short-term NTG treated groups showed no significant changes in all the parameters mentioned above as compared with the controls. Conclusion: Long-term NTG treatment, unlike short-term treatment, may cause impaired implantation and infertility, but there is also room for further improvement.